Emergence of Serotonergic Neurons After Spinal Cord Injury in Turtles - Fabbiani, Gabriela; Rehermann, María I.; Aldecosea, Carina; Trujillo-Cenóz, Omar; Russo, Raúl E. (Frontiers in Neural Circuits, 2018)
Plasticity of neural circuits takes many forms and plays a fundamental role in regulating behavior to changing demands while maintaining stability. For example, during spinal cord development neurotransmitter identity in neurons is dynamically adjusted in response to changes in the activity of spinal networks. It is reasonable to speculate that this type of plasticity might occur also in mature spinal circuits in response to injury. Because serotonergic signaling has a central role in spinal cord functions, we hypothesized that spinal cord injury (SCI) in the fresh water turtle Trachemys scripta elegans may trigger homeostatic changes in serotonergic innervation. To test this possibility we performed immunohistochemistry for serotonin and key molecules involved in the determination of the serotonergic phenotype before and after SCI. We found that as expected, in the acute phase after injury the dense serotonergic innervation was strongly reduced. However, thirty days after SCI the population of serotonergic cells (5-HT+) increased in segments caudal to the lesion site. These cells expressed the neuronal marker HuC/D and the transcription factor Nkx6.1. The new serotonergic neurons did not incorporate the thymidine analogue 5-bromo-2′-deoxyuridine (BrdU) and did not express the proliferating cell nuclear antigen (PCNA) indicating that novel serotonergic neurons were not newborn but post-mitotic cells that have changed their neurochemical identity. Switching towards a serotonergic neurotransmitter phenotype may be a spinal cord homeostatic mechanism to compensate for the loss of descending serotonergic neuromodulation, thereby helping the outstanding functional recovery displayed by turtles. The 5HT1A receptor antagonist (±)-8-Hydroxy-2-dipropylaminotetralin hydrobromide (8-OH-DPAT) blocked the increase in 5-HT+ cells suggesting 5-HT1A receptors may trigger the respecification process.